Asas Kedaulatan Rakyat Pada Undang-Undang No. 32 Tahun 2004 Jo UU No. 2 Tahun 2015 Dalam Rangka Pemilihan Kepala Daerah Secara Langsung - S. Endang Prasetyawati (Universitas Bandar Lampung (UBL), 2015)
One of existing from Democracy ground is management General Election here in after referred to as General Election. General Election Management its reality is materialization from political rights people and at one blow represent the political rights delegation to proxy those who run the governance. Research applying of Democracy ground pursuant to law 32 Year 2004 at direct execution directly regional leader election must started applied by this direct execution directly regional leader election committee, people given a break to have a finger in the pie every step directly regional leader election. Still be needed by efforts in order to society mobilization till society own the understanding concerning direct essence regional leader election and their involvement in it and also participate for awareness by their self as political maturity form with the type of autonomous participation.